Language Preservation as a Means of Society Evolution; Procedia - Social and Behavioral Sciences; Vol. 206 : Linguistic and Cultural Studies: Traditions and Innovations, LKTI - Ivankina L. I. Lyubov Ivanovna (2015, 2015)
Title screen